Lataif Perspektif Tafsir Sufi Najm al-Din al-Kubra - Ulum, Fahmi Raudhatul (Department of Ilmu al-Qur'an dan Tafsir, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2020)
Humans are created so perfectly, both given reason and lust, the war against lust applies to all mankind in the world, in this war the enemy is invisible to the eye, the enemy is very delicate, lata>’if as a means to fight the passions that must be processed as little as possible The results of this thesis are as follows: Shaykh Najmuddin Kubra in muqodimah said